Strategi pemerintah daerah dalam pemberdayaan desa wisata: Local government strategy in empowering tourism villages - Nurfadlilah, Hana Ihat; Nia Karniawati (Program Studi Ilmu Pemerintahan Universitas Mulawarman, 2023)
A tourism village is a rural area that has a special allure and is able to bring visits to tourists where more specifically a tourist village is bound by strong cultural values and traditional characteristics. When a village has been agreed upon, proclaimed as a